Essays on international trade and policy - Raza, Mian Muhammad Farrukh (Kansas State University, 2020)
Leaders around the world have introduced various trade policies including subsidies, tariffs, anti-dumping duties or price undertakings throughout the trade history. These trade policies have benefitted states in different ways. For example, some countries achieved economic development by supporting their firms through various subsidies and helping them to enhance their product qualities and become competitive in the international market. Whereas, in other cases leaders engage in imposing tariffs - a policy helps leaders to protect their producers and generate revenue. Such trade policies are not only limited to the benefits; however, they may incur costs too. As such, the imposition of trade policies affects the social welfare of all parties engaged in trade. Recently, we have seen that US-China engaged in a trade war where the United States has imposed tariff duties against China, and China responded with its tariffs on US products. This trade war has affected the social welfare one way or another. Such trade practices in the past have led scholars to address questions related to trade policies. Despite the work on trade policies, there is still a wide variety of questions yet to be answered regarding trade policies. This dissertation address three important questions related to international trade policies and their impact on social welfare. The first chapter is motivated by the observation of the quality difference between imported and local products in Pakistan. This chapter addresses the question of whether import-competing markets where foreign products are of high quality, are domestic firms doomed to produce low-quality products? What are policy options available to an importing country government that has the multiple objectives of maximizing consumer surplus, domestic profit and welfare, besides generating product quality reversal? Using a duopoly framework of vertical product differentiation, we analyze and compare three policy options: an import tariff, free trade, and a quality-upgrading R&D subsidy. We identify the conditions under which the quality-based R&D subsidy policy is a win-win-win strategy in that consumer surplus, domestic profit, and social welfare are all at their maximum levels, in addition to product quality reversal. The second chapter is motivated by the contemporary US-China trade war and its welfare implications. This paper analyzes differences in welfare implications between import tariffs and antidumping (AD) duties within a unified model of trade in quality-differentiated products under international duopoly. Specifically, the model allows for product quality choices by two competing firms located separately in a developed country (DC) and a less-developed country (LDC), where there is a different degree of international market competition. We show that dumping arises as an LDC firm sells a low-quality product that is “dumped” into the DC market. Compared to import tariffs, imposing AD duties (based on the dumping margin) by the DC government makes its firm better off. Whether DC consumers are better off and whether there is welfare improvement for DC are shown to depend on the degree of market competition. We further identify conditions under which a tariff policy is preferred over an AD policy (or the other way around) from the world perspective of welfare. The third paper investigates which types of firms (DC or LDC) tend to practice dumping, using a two-market equilibrium model of trade in “like” products with quality differentiation. Specifically, within the framework of duopolistic competition between a DC firm and an LDC firm, we show that the DC firm sells a high-quality product without practicing dumping. In contrast, the LDC firm sells a low-quality product that is dumped into the DC market at a price less than the price of the product in its LDC market. The imposition of antidumping duties by the DC government increases domestic welfare. It is welfare increasing to LDC when its exporting firm accepts a price-undertaking, rather than practicing dumping. From the perspective of world welfare, defined by aggregating the welfare of DC and LDC as trading partners, the trade damage measure of an antidumping policy is Pareto superior to free trade (under which dumping takes place) and price-undertakings.
Keywords: Trade and quality reversal; Anti-dumping duty; Price undertaking; Import tariffs; Social welfare; R&D investment